Functional Reuniens and Rhomboid Nuclei Are Required for Proper Acquisition and Expression of Cued and Contextual Fear in Trace Fear Conditioning - Chang, C.-H (NLM (Medline), 2022)
BACKGROUND: The reuniens (Re) and rhomboid (Rh) nuclei (ReRh) of the midline thalamus interconnect the hippocampus and the medial prefrontal cortex. The hippocampus and medial prefrontal cortex are both involved in the acquisition of trace fear conditioning, in which a conditioned stimulus (tone) and an aversive unconditioned stimulus (footshock) are paired but separated in time with a trace interval. Earlier, we demonstrated that ReRh inactivation during trace conditioning impaired the acquisition of cued fear. In contrast, ReRh inactivation during both conditioning and test resulted in heightened fear to tones during retrieval. Because there was a generalized contextual fear on top of heightened fear to tones in the latter experiment, here we aimed to examine the specific importance of the functional ReRh in cued fear and contextual fear through introducing prolonged contextual exposure. METHODS: The ReRh were pharmacologically inactivated with muscimol (or saline as controls) before each experimental session. RESULTS: We showed that although ReRh inactivation before trace fear conditioning impaired the acquisition of cued fear, the animals still acquired a certain level of fear to the tones. However, without the functional ReRh throughout the entire behavioral sessions, these animals showed heightened contextual fear that did not decline much with the passage of time, which generalized to the other context, and fear to tones reoccurred when the tones were presented. CONCLUSIONS: Our results suggested that functional ReRh are important for proper acquisition and expression of fear to context and tones acquired under trace procedure. © The Author(s) 2021. Published by Oxford University Press on behalf of CINP.